Knowledge and systems science enabling systemic knowledge synthesis - Nakamori, Yoshiteru (CRC Press, 2013)
"Knowledge science is a problem-oriented interdisciplinary field that explores the modeling and application of the knowledge creation process. It encompasses disciplines such as knowledge management, technology and service management, knowledge synthesis and creation, and innovation theory, with the aim of constructing a better knowledge-based society. Written by one of the leading experts in the field, this book introduces the theoretical and methodological foundations of knowledge science. It explores the human dimension in problem solving as well as the various cultural dimensions of knowledge science"--